Comparative effectiveness of three doses of weight‐loss counseling: Two‐year findings from the rural LITE trial. (November 2014) - Perri, Michael G.; Limacher, Marian C.; von Castel‐Roberts, Kristina; Daniels, Michael J.; Durning, Patricia E.; Janicke, David M.; Bobroff, Linda B.; Radcliff, Tiffany A.; Milsom, Vanessa A.; Kim, Chanmin; Martin, A. Daniel
<x xml:space="preserve">Abstract</x> Objective To evaluate the effects and costs of three doses of behavioral weight‐loss treatment delivered via Cooperative Extension Offices in rural communities. Methods Obese adults (N = 612) were randomly assigned to low, moderate, or high doses of behavioral treatment (i.e., 16, 32, or 48 sessions over two years) or to a control condition that received nutrition education without instruction in behavior modification strategies. Results Two‐year mean reductions in initial body weight were 2.9% (95% Credible Interval = 1.7‐4.3), 3.5% (2.0‐4.8), 6.7% (5.3‐7.9), and 6.8% (5.5‐8.1) for the control, low‐, moderate‐, and high‐dose conditions, respectively. The moderate‐dose treatment produced weight losses similar to the high‐dose condition and significantly larger than the low‐dose and control conditions (posterior probability > 0.996). The percentages of participants who achieved weight reductions ≥ 5% at two years were significantly higher in the moderate‐dose (58%) and high‐dose (58%) conditions compared with low‐dose (43%) and control (40%) conditions (posterior probability > 0.996). Cost‐effectiveness analyses favored the moderate‐dose treatment over all other conditions. Conclusions A moderate dose of behavioral treatment produced two‐year weight reductions comparable to high‐dose treatment but at a lower cost. These findings have important policy implications for the dissemination of weight‐loss interventions into communities with limited resources.